CONSUMER PREFERENCE FOR PALM SUGAR AND BROWN SUGAR DESIGN PACKAGING WITH KANSEI WORDS - Thamrin, Elfa Susanti; Windiastuti, Elsa; Veronika Halawa, Maria (PPPM POLTESA, 2023)
Palm sugar from farmers is generally marketed using plastic packaging and easy to melt, especially on torosan palm sugar which is located at the base of the buildup. It can be overcome by innovating in the packaging of palm sugar. This study aims to collect data related the packaging and to conduct a survey of consumer preferences for palm sugar packaging. The method used is the Kansei Engineering by collecting kansei words related to consumer preference for palm sugar packaging. After the kansei words have been collected, then the words are presented in the form of a semantic differential scale questionnaire to capture direct consumer kansei about the elements of packaging design. The samples used in this study were 18 types of palm sugar packaging. Respondents involved in the research for this initial stage were 10 consumers and 3 sugar palm farmers. The interview results obtained as many as 96 kansei words related to the packaging of palm sugar. These words are used as kansei words that will be presented in questionnaires. From the results of interviews and questionnaires can be concluded that consumers want innovation in the packaging of torosan palm sugar and brown sugar in accordance with their uses.